Boron Lewis Acid Catalyzed Hydrophosphorylation of N-Heteroaryl-Substituted Alkenes - Kwak, Soojin; Choi, Jeongin; Lee, Sarah Yunmi (Synthesis, 2024)
The hydrophosphorylation of N-heteroaryl-substituted alkenes catalyzed by a boron Lewis acid catalyst is reported. This reaction occurs with a range of alkenes bearing N-heterocycles, including pyridines, a quinoline, a pyrrole, and a benzothiazole, resulting in the production of β-N-heteroaryl alkylphosphonates in good yields under additive-free, operationally simple conditions. The mechanistic insights suggest that this hydrophosphorylation involves the deprotonation of the P–H bond of dialkyl phosphites, enabled by the cooperative effects of a boron acid and the basic N-heterocyclic moiety of the alkenes. The resulting phosphonate anion serves as an effective phosphorus nucleophile for the conjugate addition to the concurrently formed N-protonated alkenes. These β-N-heteroaryl alkylphosphonates can be further converted into other valuable organophosphorus compounds through the introduction of an alcohol group or the reduction of the phosphine oxide moiety.
Keywords: main-group chemistry; organophosphorus compounds; carbon–phosphorus bond; cooperative deprotonation